PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU KERJA INOVATIF GURU DI SMA SWASTA SE-KECAMATAN PAMIJAHAN BOGOR - Rahmawati, Ima; Ihsan, Muzhir; Fahrurrobi, Nurdin (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
Innovative work behavior is an individual action that is useful for certain organizations by recognizing a problem, coming up with new ideas, developing new ideas, and realizing every new idea with prescribed procedures. This research was conducted in private high schools throughout the Pamijahan District, Bogor Regency. This study aims to explain the effect of transformational leadership on teachers' innovative work behavior. This study uses quantitative methods with data collection techniques using a questionnaire or questionnaire. The sample used was 110 teachers, through probability sampling method with the type of proportionate stratified random sampling technique. The data analysis technique used is simple linear regression. Based on the results of the analysis, it was found that transformational leadership had a positive effect on teachers' innovative work behavior. This shows that the stronger the effect of the principal's transformational leadership, the higher the teacher's innovative work behavior will be. Therefore, to improve innovative work behavior in teachers, it is expected that there will be an increase in the indicators of transformational leadership of school principals